1998
DOI: 10.1017/s0956792598003520
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of the phase field model to its sharp interface limits

Abstract: We consider the distinguished limits of the phase field equations and prove that the corresponding free boundary problem is attained in each case. These include the classical Stefan model, the surface tension model (with or without kinetics), the surface tension model with zero specific heat, the two phase Hele–Shaw, or quasi-static, model. The Hele–Shaw model is also a limit of the Cahn–Hilliard equation, which is itself a limit of the phase field equations. Also included in the distinguished limits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
157
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(160 citation statements)
references
References 35 publications
1
157
0
1
Order By: Relevance
“…When CH is used to represent an interface that does not intersect a solid wall, as is the case for drop deformation, the sharp-interface limit is well established. [7][8][9] In such a limit, achieved at finite interfacial thickness ⑀, the results no longer depend on ⑀, and the diffusion across the interface becomes negligible. The results thus become comparable with sharp-interface computations and experiments, in which the interface is exceedingly thin, down to molecular scale.…”
Section: Introductionmentioning
confidence: 99%
“…When CH is used to represent an interface that does not intersect a solid wall, as is the case for drop deformation, the sharp-interface limit is well established. [7][8][9] In such a limit, achieved at finite interfacial thickness ⑀, the results no longer depend on ⑀, and the diffusion across the interface becomes negligible. The results thus become comparable with sharp-interface computations and experiments, in which the interface is exceedingly thin, down to molecular scale.…”
Section: Introductionmentioning
confidence: 99%
“…These computations demonstrated that for the results to be quantitatively accurate, two conditions have to be met. First, the interface should be sufficiently thin so that the theoretical model approaches the so-called sharp-interface limit [19]. Second, this thin region must be adequately resolved by fine mesh; it typically requires some 10 grid points.…”
Section: Introductionmentioning
confidence: 99%
“…Ilmanen [17] considered the corresponding L 2 -gradient flows and proved the convergence of the Allen-Cahn equation to the meancurvature flow, in the varifold formulation of Brakke [5]. Convergence of various other phase field problems to the corresponding sharp interface models have been shown either formally or rigorously [1,6,8,9,18,27,38], sometimes in quite involved weak formulations.…”
Section: Related Results and Main Techniquesmentioning
confidence: 99%